Juvenile delinquency in the urban and rural areas of the Wielkopolska region, Poland - Kulczyńska, Katarzyna; Bogacka, Emilia; Barczykowska, Agnieszka; Muskała, Maciej (Quaestiones Geographicae, 2025)
The article aims to examine the level of juvenile delinquency in the urban and rural areas of the Wielkopolska region in the years 2017–2021. Analyses were conducted by poviats1 for the Wielkopolska region. Two indicators were selected to characterise the level of juvenile crime: (1) the juvenile crime intensity indicator, which is the number of crimes committed by minors per 10,000 juveniles, and (2) the contrast indicator, which is the quotient of the intensity of juvenile crimes in urban and rural areas. Research on juvenile crime in the urban–rural context was carried out referring to four fundamental issues: (a) examining the relationship between the intensity of crime in urban and rural areas in poviats with the use of a contrast indicator, (b) determining the sequence of crime types based on the juvenile crime intensity indicator, (c) tracking changes in the level of juvenile crime over time, taking into account cities divided into three size categories: large, medium, and small (towns), and (d) analysing changes in the structure of juvenile delinquency. Research shows that the number of crimes committed by minors has slightly decreased. Criminal acts are often committed in the region’s largest cities and poviats neighbouring a large city or in poviats having a large or medium-sized city within their area. However, juvenile crime in rural areas has also increased, which is reflected in the decreasing contrast indicator. Despite the overall decline in juvenile crimes, the number of drug crimes committed by minors increased.